Respiratory compliance but not gas exchange correlates with changes in lung aeration after a recruitment maneuver: an experimental study in pigs with saline lavage lung injury - Henzler, Dietrich (BioMed Central, 2005)
INTRODUCTION: Atelectasis is a common finding in acute lung injury, leading to increased shunt and hypoxemia. Current treatment strategies aim to recruit alveoli for gas exchange. Improvement in oxygenation is commonly used to detect recruitment, although the assumption that gas exchange parameters adequately represent the mechanical process of alveolar opening has not been proven so far. The aim of this study was to investigate whether commonly used measures of lung mechanics better detect lung tissue collapse and changes in lung aeration after a recruitment maneuver as compared to measures of gas exchange METHODS: In eight anesthetized and mechanically ventilated pigs, acute lung injury was induced by saline lavage and a recruitment maneuver was performed by inflating the lungs three times with a pressure of 45 cmH(2)O for 40 s with a constant positive end-expiratory pressure of 10 cmH(2)O. The association of gas exchange and lung mechanics parameters with the amount and the changes in aerated and nonaerated lung volumes induced by this specific recruitment maneuver was investigated by multi slice CT scan analysis of the whole lung. RESULTS: Nonaerated lung correlated with shunt fraction (r = 0.68) and respiratory system compliance (r = 0.59). The arterial partial oxygen pressure (PaO(2)) and the respiratory system compliance correlated with poorly aerated lung volume (r = 0.57 and 0.72, respectively). The recruitment maneuver caused a decrease in nonaerated lung volume, an increase in normally and poorly aerated lung, but no change in the distribution of a tidal breath to differently aerated lung volumes. The fractional changes in PaO(2), arterial partial carbon dioxide pressure (PaCO(2)) and venous admixture after the recruitment maneuver did not correlate with the changes in lung volumes. Alveolar recruitment correlated only with changes in the plateau pressure (r = 0.89), respiratory system compliance (r = 0.82) and parameters obtained from the pressure-volume curve. CONCLUSION: A recruitment maneuver by repeatedly hyperinflating the lungs led to an increase of poorly aerated and a decrease of nonaerated lung mainly. Changes in aerated and nonaerated lung volumes were adequately represented by respiratory compliance but not by changes in oxygenation or shunt.